Assessing the Effect of Fertigroe® Application on the Growth and Yield of Raniag Potato Variety - Dizon, Mikhaela Kathrina H (Animo Repository, 2023)
A fertilizer is a substance incorporated into the soil to increase soil fertility, plant nutrients, and crop cultivation. However, most fast-release fertilizers available in the market engender soil deterioration, which leads to environmental degradation and food insecurity. Past researchers have analyzed the effect of numerous fertilizers on potato production, although few have explored slow-release types. In this study, experimentations were carried out to discover the efficacy of FertiGroe®, a slow-release nanofertilizer known to improve a plant’s nutrient uptake and crop yield while being less harmful to the environment. The specific objectives of this study were to compare the differences between FertiGroe®, commercially available fertilizer, and no fertilizer application in terms of the growth of Raniag potato (Solanum tuberosum) crops, and determine the effectiveness of FertiGroe® in terms of the yield produced. An experiment was conducted in the De La Salle University - Laguna Campus, wherein potato tuberlets were planted and treated varyingly using (1) FertiGroe®, (2) commercially available fertilizer, and (3) no fertilizer. In a span of 30-80 days after planting, its growth and yield parameters were recorded. The results of the experimentation showed no significant differences across the treatments. The researchers, therefore, conclude and reject the hypothesis that FertiGroe® is more effective for the growth and yield of Raniag potato crops compared to other fertilizer treatments. It is recommended that a follow-up trial be conducted to verify the result of this study.